AN ANALYSIS OF WH-QUESTIONS IN MONGONDOW LANGUAGE - Helya Mokoginta; Jennie Posumah; Fivy Andries (English Education Department, 2022)
This research aimed to determine the form and function of WH-Questions in the Mongondow language. Mongondow speakers were the subjects of this research. This research was the descriptive qualitative method. The procedure of this research consisted of selecting informants based on certain criteria, collecting through a through interviews and observations, rechecking, the data, and writing the report. The data were analyzed through unitization, categorization, explanation, and interpretation according to Bogdan & Biklen. The results of this research showed that WH-Question ns in Mongondowwasguage were formed from question words, there are 10 forms of question words commonly used in WH-Questhe tions in Mongondow language, there are Onu, Ki'ine, Onda, To'onu, Doda'anda, Nongonu, Mongonu, Pongonu, Na'anda, and Tongonu. For the function of WH-questions in Mongondow language, the question words that form WH-questions sewasas bweren the front position of the sentence in the middle of the sentence when it has a time marker verb. Onu and Onda question words that used verbs of time-marking might use the prefix conn